Structural insights into selective interaction between type IIa receptor protein tyrosine phosphatases and Liprin-α - Maiko Wakita (Nature Portfolio, 2020)
Synaptic organizers are cell-adhesion molecules capable of inducing synaptic differentiation through transsynaptic interactions. Here the authors present the crystal structure of the intracellular interaction between the synaptic organizer PTPδ and Liprin-α to reveal the structural mechanism of intracellular molecular interactions for IIa-RPTP-mediated synapse formation.